Application of diffusive gradients in thin films to determine rare earth elements in surface sediments of Daya Bay, China: Occurrence, distribution and ecotoxicological risks. (August 2022) - Gu, Yang-Guang; Huang, Hong-Hui; Gong, Xiu-Yu; Liao, Xiu-Li; Dai, Ming; Yang, Yu-Feng
Abstract: Known as burgeoning contaminants, the bioavailability of rare earth elements (REEs) can be determined using diffusive gradients in thin films (DGT). As Daya Bay (South China) has been under serious anthropogenic influences, the present study examined the distribution of REEs in surface sediments and their possible ecological risks in the bay. The range of DGT-labile concentrations of REEs (∑REEs) was from 5.67 μg/L to 8.41 μg/L, with an average of 7.34 μg/L. Results of assessment of single REE toxicity revealed that the risk quotient (RQ) values of Y, Ce and Yb were >1, indicating that their potential negative impacts on the nearby environment. However, analysis of the integral toxicity of REE mixtures through assessment of probabilistic ecotoxicological risks showed that there was a negligibly low probability of toxicity of PRE surface sediments to aquatic organisms in the study area. Graphical abstract: Unlabelled Image Highlights: Combined toxicity of REEs in sediments with DGT from Daya Bay was firstly studied. DGT-labile light REE concentrations exceeded that of heavy REE concentrations. Potential toxicities for REEs mixtures had a a negligible probability of toxic effects.